2013
DOI: 10.1186/1471-2377-13-122
|View full text |Cite
|
Sign up to set email alerts
|

Heart dysfunction in patients with acute ischemic stroke or TIA does not predict all-cause mortality at long-term follow-up

Abstract: BackgroundDespite heart failure being a substantial risk factor for stroke, few studies have evaluated the predictive value of heart dysfunction for all-cause mortality in patients with acute ischemic stroke, in particular in the elderly. The aim of this study was to investigate whether impaired heart function in elderly patients can predict all-cause mortality after acute ischemic stroke or transient ischemic attack (TIA).MethodsA prospective long-term follow-up analysis was performed on a hospital cohort con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
0
14
0
1
Order By: Relevance
“…In echocardiography, performed after acute stroke, 20-30% of stroke patients have focal or generalized contractile abnormalities, and 7% suffer from overt heart failure with left ventricular ejection fraction below 30%. 3 These features are commonly interpreted as a reflection of pre-existing heart disease rather than as a consequence of the stroke. While there is a documented history of pre-existing heart disease in some patients, longitudinal clinical studies monitoring heart function before and after stroke do not exist.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In echocardiography, performed after acute stroke, 20-30% of stroke patients have focal or generalized contractile abnormalities, and 7% suffer from overt heart failure with left ventricular ejection fraction below 30%. 3 These features are commonly interpreted as a reflection of pre-existing heart disease rather than as a consequence of the stroke. While there is a documented history of pre-existing heart disease in some patients, longitudinal clinical studies monitoring heart function before and after stroke do not exist.…”
Section: Discussionmentioning
confidence: 99%
“…Vice versa, acute stroke can affect cardiac function. A plethora of clinical manifestations comprising reduced heart rate, atrial fibrillation, cardiac dysfunction, elevated troponin, and stress‐induced acute cardiomyopathy can be found in stroke patients. Cardiac disease also contributes substantially to the long‐term prognosis of ischaemic stroke patients .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous cohort studies suggest that stroke patients with pre-existing HF have a two-to three-times higher probability to suffer severe stroke compared to patients without HF [7]. Moreover, in the majority of studies mortality has been observed to be 2-2.5-fold higher in patients with HF compared to patients without HF [5,31]. Notably, in stroke patients with HF, the risk of dying -which is about 80 % over a period of five years -is not further increased in the presence of AF [8,32].…”
Section: Relevance Of Heart Failure For Prognosis After Strokementioning
confidence: 99%
“…Die veröffentlichten (zumeist retrospektiven) Kohortenstudien zur Relevanz der (chronischen) HI für die Sterblichkeit nach Schlaganfall sind heterogen, zeigen jedoch in der Mehrzahl eine bestehende Assoziation [31] mit einem etwa 2-2,5-fach erhöhten Wahrscheinlichkeit zu sterben im Vergleich zu Schlaganfallpatienten ohne HI (zur Übersicht: 5). Interessanterweise scheint bei herzinsuffizienten Schlaganfallpatienten das additive Bestehen eines Vorhofflimmerns das Risiko zu sterben nicht weiter zu erhöhen [8,32], das über einen Zeitraum von 5 Jahren etwa 80 % zu betragen scheint [8].…”
Section: Bedeutung Einer Herzinsuffizienz Für Die Prognose Nach Einemunclassified